Missionary Photography: The Liberian Archive of Doctor Georgia Patton. (2nd October 2018) - Jenkins, Earnestine Lovelle
Abstract : This article focuses on the personal missionary experience of an African American woman physician, Dr Georgia Ester Lee Patton (1864–1900), later known as Georgia Washington. Patton worked in Liberia, a unique setting for missionary activities, being a colony established by former American slaves. The primary resource materials used here are missionary photographic archives, which comprise a distinct category of colonial cultural production. Photography assisted missions in promoting western achievements, disseminating Christianity, and advancing progress, by exposing Africans to western civilization. Such imagery was largely created by European photographers working within the social milieu of missionary organizations. Missionary photographs, therefore, functioned as an official public record of the missionary enterprise; today they are invaluable records of the histories of Christian missions around the globe. Missionary archives exist as both public and private archives. Private archives, as opposed to the images planned for a public audience, were compiled by individual missionaries and intended for private viewings. For this case study I use the private archive Patton compiled after she worked as a medical missionary in Liberia between 1893 and 1895. Patton later returned to Tennessee, where she became the first woman physician in the city of Memphis. This article seeks to determine how Patton's perception of herself as an African American, as a woman, as a Christian, and as a physician influenced her unusual experience as a medical missionary in late nineteenth-century West Africa.